Adverse Pregnancy Outcomes and Cardiovascular Disease Risk: Unique Opportunities for Cardiovascular Disease Prevention in Women. Issue 18 (4th May 2021) - Parikh, Nisha I.; Gonzalez, Juan M.; Anderson, Cheryl A.M.; Judd, Suzanne E.; Rexrode, Kathryn M.; Hlatky, Mark A.; Gunderson, Erica P.; Stuart, Jennifer J.; Vaidya, Dhananjay
Abstract : This statement summarizes evidence that adverse pregnancy outcomes (APOs) such as hypertensive disorders of pregnancy, preterm delivery, gestational diabetes, small-for-gestational-age delivery, placental abruption, and pregnancy loss increase a woman's risk of developing cardiovascular disease (CVD) risk factors and of developing subsequent CVD (including fatal and nonfatal coronary heart disease, stroke, peripheral vascular disease, and heart failure). This statement highlights the importance of recognizing APOs when CVD risk is evaluated in women, although their value in reclassifying risk may not be established. A history of APOs is a prompt for more vigorous primordial prevention of CVD risk factors and primary prevention of CVD. Adopting a heart-healthy diet and increasing physical activity among women with APOs, starting in the postpartum setting and continuing across the life span, are important lifestyle interventions to decrease CVD risk. Lactation and breastfeeding may lower a woman's later cardiometabolic risk. Black and Asian women experience a higher proportion APOs, with more severe clinical presentation and worse outcomes, than White women. More studies on APOs and CVD in non-White women are needed to better understand and address these health disparities. Future studies of aspirin, statins, and metformin may better inform our recommendations for pharmacotherapy in primary CVD prevention among women who have had an APO. Several opportunities exist for health care systems to improve transitions of care for women with APOs and to implement strategies to reduce their long-term CVD risk. One proposed strategy includes incorporation of the concept of a fourth trimester into clinical recommendations and health care policy. Abstract : Supplemental Digital Content is available in the text.